Why people commit public procurement fraud? The fraud diamond view. Issue 4 (4th November 2019) - Rustiarini, Ni Wayan; T., Sutrisno; Nurkholis, Nurkholis; Andayani, Wuryan
Abstract : Purpose: This paper aims to discuss the factors that cause individuals to commit fraud, especially in the public procurement context. All this time, an empirical review of public procurement fraud has only focused on the macro and micro level, as well as its losses on the country's economy. This paper highlights individuals' fraudulent behavior from the four elements of the fraud diamond theory, namely, pressure, opportunity, rationalization and capability. Design/methodology/approach: This paper is a literature review that discusses the fraudulent behavior of bureaucrat as a procurement official in the context of public procurement. This review uses fraud diamond theory as its theoretical framework to explain the attributes to do fraud. Findings: Public procurement is a high-risk area for fraud (corruption), particularly in the government institution. It cannot be denied that the situation factor (pressure and opportunity) will interact with psychological aspects (rationalization) and individual capability to direct the individuals to commit fraud. This study discusses how existing pressure (motivation) and opportunities are used by individuals who have the capability to rationalize their actions. This literature review also endeavors to shed light on the strategy to prevent, detect and control the causes of fraud. Practical implications: This paper provides an understanding of regulators, auditors and other employees in recognizing the characteristics and nature of fraud antecedents. This understanding can help prevent various forms of procurement fraud that occur within their organizations. This paper also can be a guideline to assist public sector organizations in designing effective internal control systems to prevent fraud in the process and practice of public procurement. Social implications: Public procurement has a central role that enables the government to allocate the budget effectively and efficiently. Compliance in implementing procurement rules and procedures will improve the quality of public services. Originality/value: There exists relatively little study outlining the factors underlying of bureaucrats' (procurement official) opportunistic behavior on procurement activities. The authors focused on bureaucrats' behavior because they have unique positions of power and responsibility of the procurement process. On the one hand, they have a crucial role in serving the public and safeguarding public assets. On the other hand, they have the ability to collaborate with politicians and business actors in corrupt procurement practices. Therefore, the discussion on this topic is very relevant and interesting.